Culturally Responsive Teaching Integrated Skill AI Based Learning Applicator to Elevate Learners Critical Thinking and Writing Proficiency - Larasati, Alika; Ginting, Pirman (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research project investigates the efficacy of combining culturally sensitive teaching with AI-based learning tools to enhance student's critical thinking and writing abilities. This project explores the potential benefits of integrating culturally responsive teaching with AI technology to enhance learners' cognitive and linguistic skills. This research employs a mixed-methods approach, utilizing quantitative and qualitative data collection approaches. The sample was collected from 15 EFL students at SMA N 10 Medan. The students were chosen to participate in the research based on their diverse cultural backgrounds. Data gathering included administering pre-and post-tests to assess students' critical thinking and writing abilities. The study shows that combining culturally responsive education with AI-based learning tools dramatically enhances students' critical thinking and writing skills. Students enrolled in AI courses experience a stimulating and culturally diverse learning atmosphere that fosters the development of their critical thinking and writing abilities. This research enhances the field of education by emphasizing the capacity of AI technology to promote culturally relevant teaching methods and enhance learners' cognitive and language abilities. The results suggest combining AI-based learning tools with culturally responsive teaching methods can improve students' critical thinking and writing skills. This study highlights the significance of incorporating cultural diversity into instructional design and offers guidance for educators and policymakers to establish inclusive and efficient learning settings.